GURNAH'S CONTRIBUTION TO POSTCOLONIAL LITERATURE AS A NOBEL PRIZE WINNER - Karimov U. N.; Jumaboeva B. A. (Bright Mind Publishing, 2025)
Prominent writer with African origin Abdurazak Gurnah was awarded with Nobel Prize in 2021 in literature “for his uncompromising and compassionate penetration of the effects of colonialism and the fate of the refugee in the gulf between cultures and continents.”. Post-colonialism is an important theme in many novels, often reflecting the author's personal experiences of displacement and cultural upheaval. In this context, the author's forced migration with his family from Zanzibar (Africa) to the UK has a profound impact, shaping narratives that explore identity, belonging and the complexities of postcolonial existence.
Keywords: Colonialism, post-colonialism, Nobel Prize, Abdulrazak Gurnah, immigrants, Africans.